The Effect of Different Agricultural Wastes on Aroma Composition of Shiitake (Lentinula edodes (Berk.) Pegler) Mushroom - Gökhan Baktemur; Zeynep Dilan Çelik; Ecem Kara; Hatıra Taşkın (Turkish Journal of Agriculture: Food Science and Technology)
Shiitake mushroom (Lentinula edodes (Berk.) Pegler) popular as both edible and medicinal, is one of the most cultivated and consumed mushroom species in the world. Cultivation of this mushroom on different agricultural wastes has been experimented in many studies until today. Nevertheless, agricultural waste trials are going on as agricultural production patterns of the countries are different. In this study, volatile aroma composition of shiitake mushroom produced on different agricultural wastes (wheat stalk, wheat bran, peanut shell, corn cob and vine pruning waste) was compared. Oak sawdust was selected as control because of its common use in literature and substrate materials were mixed at different ratios. In addition, some substrate mixtures were prepared with poplar sawdust. Volatile compounds of the shiitake mushroom were determined by using headspace-solid phase microextraction (HS-SPME) technique combined with Gas Chromatography-Mass Spectrometer (GC-MS). At the end of study, 41 volatile compounds were detected and dimethyl trisulfide, benzaldehyde, dimethyl disulfide, 1-octen-3-ol and 3-octanone were found to be dominant volatile components. Flavour and fragrance of mushrooms are dependent on many volatile aroma compounds and their proportions. While the concentration of eight-carbon components and hydrocarbons was found the highest by using wood straw, amount of sulphur containing compounds and alcohols increased by agricultural wastes in this study. In addition, corn waste positively affected aldehyde compounds.